2020
DOI: 10.3390/cancers12071919
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ras Mutations’ Prognostic Value in Metastatic Colorectal Cancer: STORIA Analysis

Abstract: Background: Colorectal cancer (CRC) is the second most common cause of cancer-specific death in both sexes in Western countries. KRAS mutations occur in about 50% of metastatic CRCs (mCRCs). The prognostic value of specific KRAS mutations still remains unexplored and unclear. Methods: Two hundred and forty KRAS wild-type and 206 KRAS/NRAS mutant consecutive unresectable mCRC patients with PS Eastern Cooperative Oncology Group (ECOG) 0 or 1, aged < 80 years, and with a life expectancy >3 months entered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Moreover, studies have shown KRAS mutation to occur in approximately 50% of patients with mCRC only. 22 Thus, studies that evaluate the clinical utility of ctDNA as a prognostic biomarker in patients with mCRC for MRD detection and predicting disease progression have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown KRAS mutation to occur in approximately 50% of patients with mCRC only. 22 Thus, studies that evaluate the clinical utility of ctDNA as a prognostic biomarker in patients with mCRC for MRD detection and predicting disease progression have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, wt KRAS patients received more CT lines (43.3% vs 20.6% in mut KRAS patients) and had a longer cumulative median time-on-therapy (20.5 vs 16.9 months in mut KRAS patients). This was indirectly related to the detrimental prognostic effect on survival of mut KRAS ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study was exploratory considering the scarcity of data about the prognostic power of different mutational evolutions of KRAS oncogene in primary vs metastatic lesions and, thus, it does not have a pre-specified study design. All patients registered in an observational database (STORIA database) ( 11 ) between 2015 and 2018 and who accepted to perform liquid biopsy before starting first-line chemotherapy were enrolled. We chose do not prolong the enrolment period to avoid any prognostic interferences related to therapeutic and methodologic changes occurring in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Among these Ras oncogenic versions, the K-Ras protein in which the glycine at codon 12 is mutated into a valine or a serine remains in the GTP-bound constitutive active form. K-Ras is associated with the worst prognosis in many cancer types [4,[35][36][37][38].…”
Section: The Expression Of the Oncogene Ras V12 Alone Is Not Sufficient To Create Neoplastic Invasive Tumorsmentioning
confidence: 99%